2011
DOI: 10.1111/j.1747-0803.2011.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Coronary Allograft Vasculopathy-A Review of Pathogenesis and Risk Factors

Abstract: Coronary allograft vasculopathy is the current leading cause for late graft loss following cardiac transplantation. Its pathogenesis is multifactorial, including immune, constitutional and genetic factors, metabolism, infection, as well as potential injury from routine immunosuppressive therapy. Children represent a patient group with unique differences: their pretransplant history rarely includes ischemic heart disease and risk factors for atherosclerotic heart disease, but many are presensitized from use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 113 publications
(228 reference statements)
0
20
0
1
Order By: Relevance
“…This finding is likely related to several issues, including the relative naiveté of the infantile immune system leading to increased graft accommodation, younger age of donors, and less frequent rejection (and specifically, rejection with hemodynamic compromise) in these patients(7,8). Furthermore, children undergoing heart transplant tend to have less obesity, diabetes, hyperlipidemia, and hypertension than do typical adult transplant recipients, thus creating a healthier host environment for graft longevity(2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is likely related to several issues, including the relative naiveté of the infantile immune system leading to increased graft accommodation, younger age of donors, and less frequent rejection (and specifically, rejection with hemodynamic compromise) in these patients(7,8). Furthermore, children undergoing heart transplant tend to have less obesity, diabetes, hyperlipidemia, and hypertension than do typical adult transplant recipients, thus creating a healthier host environment for graft longevity(2,3).…”
mentioning
confidence: 99%
“…CAV is a chronic graft complication caused by immune and nonimmune processes (2)(3)(4). Earlier studies showed that factors such as donor age, recipient age, human leukocyte antigen (HLA) mismatch, allosensitization, frequent cellular rejection, and rejection with hemodynamic compromise are associated with increased risk of CAV in children (1,(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…CAV remains a leading cause of graft loss and mortality among late survivors of heart transplantation . Despite improvements of post‐transplant management in the current era, one‐third of pediatric patients develop CAV within 10 yr of transplant .…”
mentioning
confidence: 99%
“…It is believed to be a result of chronic immune rejection and nonimmune factors like hypertension, dyslipidemia, and diabetes. 18 CAV is the leading cause of graft failure in heart transplant recipients and can be definitively treated by retransplantation only, although certain therapies such as the use of statins and incorporating sirolimus into the immunosuppression regimen have been shown to be beneficial in halting or slowing the progression of CAV. 19 Patients with more discrete stenosis undergo revascularization of the coronary arteries by angioplasty and stent placement as a palliative solution and bridge to retransplantation.…”
Section: Feature Articlementioning
confidence: 99%